Kirkpatrick, G., McMylor, P. and Fadaee, S. (Eds.) (2022). Marxism, religion, and emancipatory politics. Palgrave Macmillan (XVII+ 269 pages). ISBN: 978-3-030-91641-1. https://doi.org/10.1007/978-3-030-91642-8_4 - Gotsis, George (The Greek Review of Social Research, 2024)
Ν/Α